Morbidity Profile and Seasonal Trend in Indoor Patients in a Tertiary Care Hospital, Chandrapur - Shital S Dhoble; Devishri P Atram; Sanjay S Kubde (Medsci Publications, 2019)
Introduction: Morbidity pattern shows the magnitude of the dis- ease and time trends that highlight demographic differences and thus assists in establishment of the priorities. This survey was conducted to study a morbidity pattern and their seasonal varia- tion in indoor patients. Methodology: Retrospective study was done over a period of 1 year. 31679 patients were included using universal sampling method. Data was collected from medical record department and diagnosis was made as per international classification of diseases 10(ICD 10). Data was analyzed. Results: out of the total 31679 patients, 66.43% were females. Sea- sonal trend analysis shows peak in admission in monsoon season. 81% admitted patients were from Chandrapur district while 17% were from outside Chandrapur. Present study shows that 10101 (31.89%) patients were admitted under chapter XV followed by chapter I constituted 15.04%. cataract was the most common mor- bidity (10%) of total patients having female preponderance (54.52%) followed by anaemia and Acute gastroenteritis (8.47%) and (4.51%) with female preponderance (66.32%), (58.49%) respec- tively. Conclusion: Cataract, anaemia and AGE are leading cause of mor- bidity.